PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN AKUNTANSI PERTANGGUNGJAWABAN TERHADAP KINERJA MANAJERIAL - Qadriyanti, Nisrinah Laila (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the influence of participation in budgetary and responsibility accounting to the managerial performance. This research is conducted in Health Department of Surabaya by using quantitative research. The multiple linear regressions are applied as the data analysis model. The examination of data quality is carried out by using validity test and reliability test and then the classic assumption test which is applied in this research is the normality test, heteroscedaticity test, multicolinearity test and autocorelation test. The result of this research indicates that the participation in the budgetary has no influence to the managerial performance, while the accounting responsibility has an influence to the managerial performance.Keywords: Participation in the Budgetary, Accounting Responsibility, Managerial Performance.